2011
DOI: 10.1159/000331013
|View full text |Cite
|
Sign up to set email alerts
|

Child Overweight – Mothers’ Competence to Take Action

Abstract: Objective: We investigated mothers’ possession and display of action competence to counteract or prevent overweight and eventual obesity in their children. Action competence is defined as a personal resource where the most important aspect is the individual’s wish to take action and to believe in its benefit. It unfolds within the room for action as experienced by the individual due to action obstacles and action potentials. Methods: In a case-control study, mothers of 111 overweight children (MOC) were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The study was a cross sectional case-control one conducted as part of an investigation of mothers’ wishes and abilities to counteract overweight among their seven to nine year old children. 22 , 23 Mother-child pairs were recruited from The Danish National Birth Cohort (DNBC) 24 established when the mothers were pregnant. Initially 101 thousand mothers were included, each having been interviewed five times in the period to the children’ seventh birthdays.…”
Section: Methodsmentioning
confidence: 99%
“…The study was a cross sectional case-control one conducted as part of an investigation of mothers’ wishes and abilities to counteract overweight among their seven to nine year old children. 22 , 23 Mother-child pairs were recruited from The Danish National Birth Cohort (DNBC) 24 established when the mothers were pregnant. Initially 101 thousand mothers were included, each having been interviewed five times in the period to the children’ seventh birthdays.…”
Section: Methodsmentioning
confidence: 99%
“…To be able to counteract the epidemic of childhood obesity and its adverse effects [3,7,8], it is important to understand the parents' opinions about the weight of their children, and it is a key step in forming effective liaisons between health professionals and parents [9]. To understand whether and how mothers play out action to counteract overweight in their children -which we reported in a joint publication [10] -it would be helpful to know whether the mothers are aware of the overweight in their children. Studies from the UK [11,12], Italy [13], USA [14,15], Canada [16] and Australia [17,18] have shown that parents are unconcerned and unaware of their children's weight status as being overweight or obese [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%